Geospatial evaluation of San Francisco, California’s homeless encampment sweeps injunction - Sean G. Young; Vincent Truong; William P. Watson; Cari A. Bogulski (Frontiers in Public Health)
IntroductionHomelessness remains a pervasive issue in many communities within the United States (US). “Sit-lie” policies restrict where individuals can sit or lie down in public places and are frequently passed and cited to forcibly re-locate individuals experiencing homelessness. In December 2022, a federal judge issued a temporary injunction of San Francisco, California’s sit-lie policy, due to a pending lawsuit arguing that the enforcement of such policies when shelter cannot be offered is a violation of the Eighth Amendment of the US Constitution.MethodsTo examine the effects of this preliminary injunction, we spatially examined data from San Francisco’s 311 reporting system to identify encampment report hot spots.Results and discussionOverall, we found spatial shifting of encampment reporting, but fewer reports overall during the preliminary injunction period, relative to 1 year prior. Future work should examine the effect of the reversal of the injunction following a recent Supreme Court decision and subsequent ruling by the Ninth Circuit Court of Appeals.